Comic drunks, crazy cults, and lovable monsters : bad behavior on American television - Diffrient, David Scott, 1972- (Television and popular culture., 2022)
"Diffrient explores the ways in which social imaginaries related to "bad behavior" have been humorously exploited over the years through his examination of a broad range of network and cable TV shows across the history of the medium"--